MULTIMEDIA APPLICATIONS ANIMATED MARKETING SHOP SURVEY RESULTS USING MACROMEDIA FLASH 8 - Zaenuddin Achmad; Hariyanto Hariyanto Skom, MMsi (Jurnal Sistem Informasi, 2008)
Animation frequently encountered only in the world of entertainment and butanimation can also be used in other fields. For example in the world of business andtrade. With animation, the delivery to another party will not be boring.Animation applications is expected to help marketing the store to be able to explainthe survey results, based on which the can from the field.In writing this research will be discussed how to make an animated multimediamarketing survey results are simple and interesting shops. This animation createdusing Macromedia Flash 8 application program. Where Macromedia Flash is oftenused to create animations in the world of entertainment (entertainment).